2010
DOI: 10.1111/j.1365-2133.2010.09756.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effect of prolactin-induced protein: a new insight into its local and systemic role in chronic allergic contact dermatitis

Abstract: These findings suggest that PIP might have a local and systemic immunosuppressive effect in mouse chronic ACD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, antibody blockade of CD23 inhibited the increase of splenic MCs (data not shown), suggesting the possible involvement of this low affinity IgE receptor. IgE engagement of CD23 on monocytes (which infiltrate the spleen upon oxazolone challenge (Sugiura et al, 2010)) has been shown to induce secretion of CCL3 (Ezeamuzie et al, 2009), a potent chemoattractant for MCs. Collectively, these findings demonstrate a connection between the spleen and the skin in modulating chronic allergic dermatitis, and the putative trafficking of Tregs between the two sites warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, antibody blockade of CD23 inhibited the increase of splenic MCs (data not shown), suggesting the possible involvement of this low affinity IgE receptor. IgE engagement of CD23 on monocytes (which infiltrate the spleen upon oxazolone challenge (Sugiura et al, 2010)) has been shown to induce secretion of CCL3 (Ezeamuzie et al, 2009), a potent chemoattractant for MCs. Collectively, these findings demonstrate a connection between the spleen and the skin in modulating chronic allergic dermatitis, and the putative trafficking of Tregs between the two sites warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…PIP is an immunosuppressive molecule. 17,18 Differentially expressed genes in responders to fumaric acid esters…”
Section: Differentially Expressed Genes In the Skin Of Patients With ...mentioning
confidence: 99%
“…Basmaciogullari et al (2000) suggested that binding between PIP and CD4 blocks the CD4-HLA-DR interaction. Moreover, PIP has a local and systemic immunosuppressive effect in mouse chronic allergic contact dermatitis (Sugiura et al, 2010). However, the biological function of the aspartic peptidase residues of human PIP has not been identified.…”
Section: Introductionmentioning
confidence: 99%